2016
DOI: 10.1016/j.jhazmat.2016.03.090
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of arsenic speciation and bioaccessibility in mine-impacted materials

Abstract:  Different mine materials have statistically dissimilar As bioaccessibility values  As bioaccessibility is dependent on As and Fe speciation and particle size  As:Amorphous Fe molar ratio describes As bioaccessibility in calcinated materials  Default RBA values may not be appropriate for different mine-impacted materials Manuscript word count: 4625

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 38 publications
(64 reference statements)
4
28
3
Order By: Relevance
“…The concentration of As was the highest in CMW (15240±190 mg/kg), followed by SH15 (2010±17.2 mg/kg) and PP (160±0.8 mg/kg). Similar to CMW, elevated As concentrations in soil samples from gold mining regions have been reported previously (Meunier et al, 2010) and may be associated with the sulphidic phases in gold ores (Ollson et al, 2016). The results of speciation analysis demonstrated that the majority of the As present in all three samples was sorbed species (70-90%) with the remainder present as scorodite and beudantite ( Table 2).…”
Section: Physico-chemical Characteristics Of Mining/smelting Impactedsupporting
confidence: 68%
“…The concentration of As was the highest in CMW (15240±190 mg/kg), followed by SH15 (2010±17.2 mg/kg) and PP (160±0.8 mg/kg). Similar to CMW, elevated As concentrations in soil samples from gold mining regions have been reported previously (Meunier et al, 2010) and may be associated with the sulphidic phases in gold ores (Ollson et al, 2016). The results of speciation analysis demonstrated that the majority of the As present in all three samples was sorbed species (70-90%) with the remainder present as scorodite and beudantite ( Table 2).…”
Section: Physico-chemical Characteristics Of Mining/smelting Impactedsupporting
confidence: 68%
“…Speciation of metal(loid)s of interest (As, Fe and Pb) was determined using X-ray absorption spectroscopy (XAS) (MRCAT beamlines 10-ID (Pb) and 10-BM (As and Fe), Sector 10 (Segre et al, 2000;Kropf et al, 2010), at the Advanced Photon Source of the Argonne National Laboratory, U.S) according to methodologies detailed in (Ollson et al, 2016).…”
Section: Physico-chemical Characterizationmentioning
confidence: 99%
“…Indeed, As is oxidised to arsenite to then precipitate during roasting from vapours to become As 2 O 3 . Several studies report an association of As with gold deposits containing sulphide minerals (Antwi-Agyei, Hogarh, & Foli, 2009;Bisone et al, 2016;Chakraborti et al, 2013;Houben, D'Onofrio, Kokelj, & Blais, 2016;Nyanza, Dewey, Thomas, Davey, & Ngallaba, 2014;Ollson, Smith, Scheckel, Betts, & Juhasz, 2016;Ono, Tappero, Sparks, & Guilherme, 2016;Toujaguez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%